Clinical value of the caval–aortic index and inferior vena cava diameter for volume assessment in hypernatremic patients - Tuba Şafak; Ahmet Burak Erdem (PLOS One, 2026)
Background Accurate assessment of intravascular volume status in hypernatremic patients presenting to the emergency department is often challenging due to advanced age, altered mental status, and unreliable physical examination. Bedside ultrasonography may provide rapid, noninvasive support for early volume evaluation. This study aimed to assess the clinical utility of inferior vena cava (IVC) diameter and the IVC-to-aorta (IVC/Ao) ratio in relation to early sodium response in patients with hypernatremia. Methods This prospective observational study included 60 adult patients with hypernatremia presenting to a tertiary emergency department. Ultrasonographic measurements (IVC diameter, aortic diameter, and IVC/Ao ratio) and manometric measurements (central and peripheral venous pressures) were obtained before fluid resuscitation and repeated at the third hour of treatment. Early sodium response was exploratorily assessed using the 3-hour change in serum sodium (ΔNa 1 ). Receiver operating characteristic analysis was used to determine the optimal ΔNa 1 cut-off associated with 30-day mortality. Results Patients without early sodium response (n = 42) had significantly higher baseline IVC/Ao ratios than patients with early sodium response (0.74 vs. 0.50, p = 0.037). Ultrasonographic parameters, including baseline and 3-hour IVC diameter and IVC/Ao ratio, demonstrated moderate discriminative performance for predicting early sodium response (AUC range: 0.671–0.683), whereas manometric measurements did not significantly differ between groups. These indices demonstrated high sensitivity but modest specificity for early sodium response. Conclusion In hypernatremic patients, bedside ultrasound assessment of IVC diameter and IVC/Ao ratio may provide rapid, complementary physiologic information during early volume evaluation. These measurements should be interpreted alongside clinical and laboratory findings rather than as standalone indicators of treatment success.